Swallow syncope after orthognathic surgery: A case report - Vinicius Balan Santos Pereira; Joaquim Celestino da Silva Neto; Davi da Silva Barbirato; Belmiro Cavalcanti do Egito Vasconcelos (Elsevier, 2022)
Swallowing syncope is a neurological eating disorder associated with severe transient heart disorders. This case report aimed to describe a rare case of swallowing syncope after orthognathic surgery.